Implementasi Pembelajaran Tematik Berbasis Active Learning Dalam Meningkatkan Minat Belajar Siswa SD Al-Qur’an Daarul Fatah Sribhawono - Bimantoro, Adi; Mahmudah, Masrurotul; Aisyah, Nurul (CV. Creative Tugu Pena, 2024)
This research aims to find out how thematic learning based on active learning can increase students' interest and learning outcomes in the material on vegetative plant propagation in class III of SD Al-Qur'an Daarul Fatah Sribhawono. This research is descriptive qualitative research, data collection was carried out using interview, observation and documentation methods. In this case, the data analysis used by researchers is descriptive analysis using deductive and inductive thinking. Research is carried out by collecting and compiling data, analyzing it, then interpreting the data, then drawing conclusions and using deductive and inductive thinking methods. Meanwhile, data validity testing was carried out by data triangulation. The results of this research indicate that the implementation of thematic learning based on active learning for class III Marwah at SD Al-Qur'an Daarul Fatah Sribhawono was carried out directly. In its implementation, students experience an increase in interest in learning, which can be seen from indicators of interest in learning, namely feelings of joy, interest in learning, showing attention when studying, and involvement in learning. Thematic learning, especially science content, becomes more meaningful and concrete because it involves students directly. Keywords: Thematic Learning, Active Learning, Students Interest